The impact of relationship marketing on consumer behavior by application to DAL Company (Economic studies journal, 2020)
The research problem was that the consumer behavior of Dal Food Company suffers from fluctuation, and this may be caused by relationship marketing. The research problem is represented in the following questions: Is there an effect of relationship marketing on consumer behavior in Dal Food Company? What is the impact of language and the extent of the impact of communication? Is there an effect of commitment? And to what extent does empathy affect? What is the effect of exchange? Is there an effect of personality on consumer behavior? The research aimed to examine the impact of relationship marketing on consumer behavior at Dal Food Company. And knowing the impact of language. And recognize the impact of communication. And study the impact of commitment. And research the effect of empathy. And know the effect of reciprocity. As well as studying the impact of personality on consumer behavior at Dal Foodstuff Company. The research tested the following hypotheses: There is an effect of relationship marketing on consumer behavior at Dal Foodstuff Company. There is a trace of language and there is a trace of communication. There is an effect of commitment. There is a trace of empathy. There is an effect of reciprocity. There is an impact of personality on consumer behavior at Dal Foodstuff Company. The research followed: the descriptive analytical approach, the historical approach, and the use of the social survey program SPSS. The study reached the following results: The study proved that there is a statistically significant relationship between relationship marketing and consumer behavior. The study proved that there is a relationship Statistically significant between language and consumer behavior. The answers of the respondents ranged in approval rates between 86% and 70%. The study proved that there is a statistically significant relationship between communication and consumer behavior. The answers of the respondents ranged in approval rates between 86% and 70%. The study proved that there is a statistically significant relationship between commitment and behavior. Consumer. The answers of the respondents ranged with approval rates between 82% and 68%, and the study proved that there is a statistically significant relationship between empathy and consumer behavior. The respondents’ answers ranged in agreement between 82% and 66%. The study proved that there is a statistically significant relationship between reciprocity and consumer behavior. The answers of the respondents ranged with approval rates between 78% and 60%, and the study proved that there is a statistically significant relationship between personality and consumer behavior. The answers of the respondents ranged with approval rates between 78% and 54%. The study also recommended the following: making more efforts while maintaining the methods followed now, with a focus on developing the dimension ofPersonal and mutual training and development